Subthreshold CMOS voltage reference - Zhong, Huishu (2016)
Low dropout regulator (LDO) plays a very significant role in many electronica systems. This paper is aimed to introduce a low dropout regulator with embedded voltage reference for low power biomedical system. Before designing a LDO, many practical issues need to be considered, such as big size of the implant, limited operating lifetime, and temperature limitation. Therefore, this paper aimed to introduce a good performed LOD designed with 0.18um CMOS technology, which can provide a low power consumption and low temperature coefficient. Compare with conventional LDO, this low dropout regulator with embedded voltage reference have all the transistors work in a sub threshold region, so that the LDO require a very small leakage current to give a stable output voltage, meanwhile the power consumption is very small. So this LDO will provide a long lifetime for low power biomedical systems. Due to the technology limitation, the first order temperature coefficient is not good enough when the temperature is high, hence the seconder effect temperature coefficient is brought into this LDO to improve (reduce) the temperature coefficient for high temperature. So this LDO will provide a stable output voltage with various temperatures.